EFEKTIVITAS PENJATUHAN SANKSI ADAT TERHADAP TINDAK PIDANA PENCURIAN YANG BERKELANJUTAN - Nike Arnis Bu'ulolo (LPPM Universitas Nias Raya, 2024)
Theft is a criminal act that is prohibited by both written and unwritten laws which causes unrest among the community. One of the crimes of theft which was resolved according to customary law by the traditional head (Si'ulu, Si'ila), village government and community leaders occurred at the researcher's research location in Lolomli village, Mazino sub-district, South Nias. area. In this decision the perpetrator was sentenced to punishment in the form of customary sanctions. The customary sanction is a fine of Rp. 2,000,000 (two million rupiah) for the actions he committed. The type of research used is sociological legal research using a statutory approach and a case approach. Data collection was carried out using primary data. Primary data is data that is still raw or data that has not been processed and obtained by researchers directly from the field. Primary data was collected through observation, interviews and document study. The data analysis used is qualitative descriptive analysis and conclusions are drawn using deductive methods. Based on the results of the research and discussion, it can be concluded that imposing customary sanctions on perpetrators of continuous theft crimes is effective because in the first (1) and second (2) acts of theft committed by the perpetrator, the victim did not take any action. reported it to the Lolomboli village government, Mazino sub-district, South Nias district. However, in the third act (3), the victim reported it to the village government and was subject to customary sanctions in the form of a fine of Rp. 2,000,000 (two million rupiah) through the village customary institution (LAD). So the researcher's suggestion is that the village government can make village regulations (Perdes) regarding the imposition of customary sanctions for criminal acts of theft..